CHINESE CINDERELLA AND HER RUSSIAN “SISTERS” (COMPARATIVE ANALYSIS OF FAIRY TALES TYPE ATU 510A) (Philological Studies, 2021)
The article compares the Chinese and Russian versions of fairy tales related to the plot type of ATU 510A “Cinderella”. The Chinese history of “Ye Xian” is known as part of a literary monument of the IX century; Russian texts having a folklore nature appeared much later, in the XIX century. Their comparison allows us to identify common plot elements and culturally determined differences. In addition, the inclusion of a literary monument with oral origins in the corresponding typological series of folklore works reveals the range of “narrative perspectives” of the plot: the set of possible variations of narrative elements and their semantic possibilities becomes more obvious. The Chinese version of “Cinderella” has obvious genre features of a fairy tale: its main character is an orphan girl who is rewarded in the end by marriage with the ruler, who found her by the shoe she lost. The plot of “Ye Xian” is a contamination with another plot type: in the first part of the fairy tale, the main character receives help from the bones of a magic animal (a large fish, which she took care of). At the same time, the narrative frame models the fairy tale as the life story of a particular girl who belonged to the Dong people. A peculiar violation of the narrative laws of a folk tale can be seen in the fact that after the wedding, the life of the main character is pushed to the periphery of the plot, and the events associated with her husband, the ruler of the island, are in the center. The Chinese version is also interesting because it includes signs of a different genre – an etiological legend: the story of Ye Xian becomes an explanation of the local toponym and the revered object named by it (the legendary grave of a stepmother and her daughter, where people came to ask for a good bride). The appendix to the article includes the author's translation of the fairy tale “Ye Xian” from Chinese into Russian.